Single-use suvorexant for treating insomnia during overnight polysomnography in patients with suspected obstructive sleep apnea: a single-center experience - Matsumura T; Terada J; Yoshimura C; Koshikawa K; Kinoshita T; Yahaba M; Nagashima K; Sakao S; Tatsumi K (Dove Medical Press, 2019)
Takuma Matsumura,1 Jiro Terada,1 Chikara Yoshimura,2 Ken Koshikawa,1 Taku Kinoshita,1 Misuzu Yahaba,1 Kengo Nagashima,3 Seiichiro Sakao,1 Koichiro Tatsumi1 1Department of Respirology, Graduate School of Medicine, Chiba University, Chiba, Japan; 2Department of Respiratory and Sleep Medicine, Fukuoka University School of Medicine, Fukuoka, Japan; 3Research Center for Medical and Health Data Science, The Institute of Statistical Mathematics, Tokyo, Japan Purpose: Although patients with suspected obstructive sleep apnea (OSA) might suffer difficulty in falling asleep during overnight polysomnography (PSG), standard hypnotics to obtain sleep during PSG have not been established. The aim of this study was to investigate the safety and efficacy of a new hypnotic agent, suvorexant, a dual orexin receptor antagonist, for insomnia in suspected OSA patients during in-laboratory PSG.Patients and methods: An observational study was conducted during PSG for 149 patients with suspected OSA who had no insomnia at home. Patients with difficulty in falling asleep during PSG were optionally permitted to take single-use suvorexant. Patients with residual severe insomnia (>1 hour) after taking suvorexant were permitted to take an add-on use zolpidem. Clinical data and sleep questionnaire results were analyzed between a no insomnia group (without hypnotics) and an insomnia group (treated with suvorexant).Results: Among 84 patients who experienced insomnia during PSG and required hypnotics (the insomnia group; treated with suvorexant), 44 (52.4%) achieved sufficient subjective sleep with single-use of suvorexant, while the other 40 (47.6%) required suvorexant plus zolpidem. An apnea hypopnea index (AHI) of ≥5 was observed in 144 out of 149 patients with predominantly obstructive respiratory events. Among those patients, 70.8% in the no insomnia group and 63.1% in the insomnia group had severe OSA. Regarding both subjective sleep time and morning mood, significant differences between the no insomnia group and the insomnia group were not observed. No patient taking suvorexant had an adverse event, such as delirium or falling.Conclusion: Single-use suvorexant seems to be a safe and effective (but mild) hypnotic agent for suspected OSA patients with insomnia during in-laboratory PSG. Keywords: insomnia, suvorexant, polysomnography, obstructive sleep apnea, zolpidem, natural sleep